2017
DOI: 10.1080/14606925.2017.1352922
|View full text |Cite
|
Sign up to set email alerts
|

CO/DEsign: building a shared dialogue around analysis within co-design

Abstract: In times of rapid social, economic, environmental and technological change designers can play a valuable role by applying their creativity to catalyse innovative solutions to address complex problems. As they do so, it becomes apparent they need to ask fundamental questions about what they make, how they make it, and who for. The mindsets and postures of designers often go unnoticed and unacknowledged, but they profoundly influence what is identified as a problem and how it is framed and addressed. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…Dependability, referring to the stability of findings, also clashes with the participatory focus on ongoing dialogue that could lead to changes over time. In the field of Design, methods are evaluated based on the extent to which they enable participants to explore their own needs, and support collective meaning‐making, 24,50 which we argue was achieved here. In the PPI literature, authors have suggested that trustworthiness in the context of two‐way learning is about answering the question ‘did the interaction lead to a change?’ 51 and transparently reporting changes in the researcher's thinking 52 rather than about evidencing contributors' thoughts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dependability, referring to the stability of findings, also clashes with the participatory focus on ongoing dialogue that could lead to changes over time. In the field of Design, methods are evaluated based on the extent to which they enable participants to explore their own needs, and support collective meaning‐making, 24,50 which we argue was achieved here. In the PPI literature, authors have suggested that trustworthiness in the context of two‐way learning is about answering the question ‘did the interaction lead to a change?’ 51 and transparently reporting changes in the researcher's thinking 52 rather than about evidencing contributors' thoughts.…”
Section: Discussionmentioning
confidence: 99%
“…After each workshop, the lead researcher completed field notes and shared a written summary of the discussions, which contributors could add to or revise. Workshops were not audio‐recorded, to focus more on active recording of feedback within the workshop, as interactive design tools can capture richer data compared to transcripts in codesign settings 24 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inductive thematic analysis was performed by the research team using the data transcripts [ 24 ]. This inductive method was chosen for its lack of assumptions regarding the patterns of meaning contained within the data [ 24 ] and is a method commonly employed in co-design research [ 25 26 27 ]. Analysis was conducted in parallel with data collection to ensure that any issues raised are explored in co-design sessions in the development of the solution.…”
Section: Methodsmentioning
confidence: 99%
“…En cohérence avec les approches de design participatif et d'agentivité transformatrice, l'identification des thèmes émergents a été réalisée et négociée pendant les rencontres, plaçant les participantes dans une posture de praticiennes, de chercheuses et de conceptrices : « The design/research blur will be disruptive at first, with arguments going back and forth about who is best suited to do what, which tools and methods belong to whom and how to analyze the data » (Sanders et Stappers, 2008, p. 13). L'analyse a été menée en contexte de design et d'investigation, poursuivant ainsi le dialogue partagé amorcé au niveau de l'analyse des données (Johnson, Ballie, Thorup, Brooks et Brooks, 2017) par une validation à postériori du contenu des grilles produites durant les trois ateliers.…”
Section: L'analyse Des Donnéesunclassified